Reconceiving Infertility: Biblical Perspectives on Procreation and Childlessness - Moss, Candida R. (Princeton University Press, 2015)
In the Book of Genesis, the first words God speaks to humanity are "Be fruitful and multiply." From ancient times to today, these words have been understood as a divine command to procreate. Fertility is viewed as a sign of blessedness and moral uprightness, while infertility is associated with sin and moral failing. Reconceiving Infertility explores traditional interpretations such as these, providing a more complete picture of how procreation and childlessness are depicted in the Bible. Closely examining texts and themes from both the Hebrew Bible and the New Testament, Candida Moss and Joel Baden offer vital new perspectives on infertility and the social experiences of the infertile in the biblical tradition. They begin with perhaps the most famous stories of infertility in the Bible-those of the matriarchs Sarah, Rebekah, and Rachel-and show how the divine injunction in Genesis is both a blessing and a curse. Moss and Baden go on to discuss the metaphorical treatments of Israel as a "barren mother," the conception of Jesus, Paul's writings on family and reproduction, and more. They reveal how biblical views on procreation and infertility, and the ancient contexts from which they emerged, were more diverse than we think. Reconceiving Infertility demonstrates that the Bible speaks in many voices about infertility, and lays a biblical foundation for a more supportive religious environment for those suffering from infertility today.